KARAKTERISTIK PENDERITA DIABETES MELLITUS TIPE 2 DENGAN KOMPLIKASI YANG DIRAWAT INAP DI RUMAH SAKIT UMUM DAERAH (RSUD) GUNUNGSITOLI TAHUN 2015 - Maria Margareth Zebua; Hiswani .; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Diabetes Mellitus (DM) is a chronic metabolic disease. According to International Diabetes Federation (2015), global prevalence of DM in adults aged 20-79 years reached 8,8%. Prevalence in Indonesia according to World Health Organization (2016) reached 7,0%. In North Sumatera, prevalence of DM was 1,8% in 2013. The purpose of this research is to find out the characteristics of patients type 2 DM with complications who were hospitalized at Gunungsitoli Hospital in 2015. This study is descriptive with case series design. The population and sample were 142 people. The data was using secondary data and analyzed by using Chi-Square, Exact Fisher and Mann-Whitney. The result showed the proportion of patients with complications of type 2 DM was highest at the age group 45-54 years is male (41,0%) of all male patients and female (45,7%) of all female patients, Nias (95,8%), Christiant Protestant (89,4%), civil servants (29,6%), married (80,3%), live in Gunungsitoli (64,1%), languid/nausea and vomit (31,7%), hypertension (33,1%), the checking blood plasma glucose (64,1%), the abnormal levels of blood plasma glucose (78,0%), oral hypoglycemic medicine (78,2%), government cost (97,9%), average length of stay (8 days), becoming outpatient (84,5%). The statistical resulted, there was no difference between age by the category of complication (p=1,00), gender by the category of complication (p=0,375), medical management by the category of complication (p=530), average length of stay by the category of complication (p=0,620). It’s suggested for Gunungsitoli Hospital to check blood plasma glucose for the patients of type 2 DM, and plan a medical management appropriate. The patient of type 2 DM with complications should control blood glucose regularly, adopt healthy lifestyle and put the treatment with insulin. Keywords: Characteristic, Type 2 DM, Gunungsitoli Hospital